HAK ROYALTI DALAM INDUSTRI MUSIK: ANALISIS PERLINDUNGAN HUKUM TERHADAP PENCIPTA LAGU TERKAIT COVER LAGU: Royalty Rights in The Music Industry: Legal Protection Analysis For Songwriters Regarding Cover Songs - Rogate, Luvito (Fakultas Hukum, Universitas Trisakti, 2024)
The purpose of this research focuses on the concept of royalty rights for songwriters and its implications in the music industry. As works of art, songs are protected by copyright which includes the economic and moral rights of the creator. Unauthorized use of songs, such as in the creation of cover songs, raises various issues related to royalties. Royalties are the compensation that creators must receive as a form of appreciation for the commercial use of their work. This study also highlights the importance of legal protection and an effective royalty payment system to safeguard the rights of songwriters and musicians. Without adequate protection, songwriters may not be properly compensated for their works, which could be detrimental to creativity and innovation in the music industry. In addition, this research underscores the need for regulatory adjustments and updates to address issues that arise with the development of technology and digital media, such as platforms that are often used to publish cover songs. These issues require special attention to ensure that the royalty management system works well and songwriters get their due fairly. This research provides an in-depth look at the need for a transparent and fair system in royalty management to support the sustainability of the music industry and